Product development: in-house innovation or international clone? A research on different performance of technology start-ups in Vietnam - Le, Thai Phong; Le, Hong Ngoc Han (Journal of International Economics and Management, 2015)
New product development (NPD) is one critical stage deciding the nature and the success of a start-up company. This research aims to compare the effectiveness of two approaches: innovation and international clone in NPD of technological start-ups in Vietnam. The paper utilises bothexploratory case study research and in-depth interview research methods and revealed that in-house innovative products perform better generally but not as stable as the copycats. This trend is obvious in revenue and compounded annual growth rate, but in profit, both kind of product fluctuated and have opposite direction. There is no guarantee of success no matter what approach entrepreneurs follow. On the other hand, qualitative findings show that there is significant intersection between innovative and copycat products that make it harder to decide which one is more efficient. However, best practice in Vietnam should be copying new concept in the short term then innovating on the copycats to match the market and win the long run. Hence, a clever combination of innovation and reference would lead to more chance of success. For sustainable development of the company and the economy, innovation is a critical approach that cannot be dismiss now and in the future. It is the heart of entrepreneurship and the new product development, too. The paper sheds more light, academically and practically, to the importance of the combination of different ways of innovation in order to improve business performance in Vietnamese context